Analisis Pengaruh Sektor Pariwisata Terhadap Penyerapan Tenaga Kerja - Agustina, Putri Wulan; Huda, Syamsul; Perdana, Putra (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
This research aims to determine the effect of the number of tourists, hotel occupancy rates, and number of tourist attractions on work energy absorption in Banyuwangi Regency, Pasuruan Regency and Batu City. The method used in this research is a quantitative research method with panel data regression analysis method through the eviews12 program. Using secondary data at BPS (Central Statistics Agency), the various regions studied in 2013-2022 were carried out using the selected model, namely the Random Effect Model (REM). The results of the analysis show that overall the independent variables (Number of Tourists, Hotel Occupancy Level, Number of Tourist Attractions) have an influence on labor absorption in Banyuwangi Regency, Pasuruan Regency and Batu City. Partially, the variable number of tourists has no effect on work energy absorption, the hotel occupancy rate variable has no effect on work energy absorption, while the number of tourist attractions has an effect on work energy absorption in the tourism sector in Banyuwangi regency, Pasuruan regency and Batu city.